CODE- SWITCHING AS AN EFL INSTRUCTIONAL STRATEGY: AN INSIGHT TO INDONESIAN LECTURERS’ PRACTICES - Rahmah Fithriani (Universitas Islam Sumatera Utara (UISU), 2021)
Studies on code-switching (CS), particularly in Indonesian EFL context have a proclivity for the occurrences i.e., its types and forms being produced by the speakers, few on their motives of practising it. This study aims to fill the void by examining Indonesian EFL lecturers’ practices of CS in General English classes for first-year university students from typological and functional points of view. Involving participant observation and interview as the instruments for data collection, the results reveal that the two lecturers participated in this study employed three types of CS, namely inter-sentential switching, intra-sentential switching, and tag-switching (ordered accordingly from the mostly to the least used type). Furthermore, it is also found that the lecturers’ practises of CS served three pedagogical functions: 1) to enhance students’ comprehension; 2) to scaffold students’ learning; and 3) to encourage students’ participation. Findings suggest that strategic use of CS in instructional practices may enhance EFL teaching as well as maximize learning efficacy.